Instruções dadas por D. Jorge da Costa, Cardeal de Portugal, em Roma, a Francisco Fernandes, que enviava a D. Manuel I, Rei de Portugal (1496) - Martins, Diana Neves (2021)
SFRH/BD/143626/2019 UIDB/00749/2020 UIDP/00749/2020